Узагальнена модель керування технологічним процесом електророзрядного синтезу нановуглецю - Назарова, Наталя Станіславівна; Вінниченко, Дмитро Валерійович; Козирєв, Сергій Сергійович; Овчиннікова, Лариса Єфремівна; Чущак, Сергій Володимирович (НТУ "ХПІ", 2016)
Проведено аналіз технологічного процесу електророзрядного синтезу нановуглецю як об’єкта керування. Побудовано узагальнену модель керування технологічним процесом високочастотного електророзрядного синтезу вуглецевих наноматеріалів з вуглецевмісного газу у вигляді графа, у якому технологічні підгрупи операцій відповідають гілкам, а стійкі стани – вершинам графа. Визначено координати векторів стану. Це дає змогу технологічний процес представити фрагментарно, та використовуючи метод декомпозиції, задачу керування розкласти на декілька задач різного рівня, кожна з яких відноситься до певного фрагменту технологічного процесу, незалежна, має свої критерії оптимальності та алгоритми реалізації.

The analysis of the process of an electric synthesis of nanocarbon as a control object was done. A generalized model of process control high-frequency electric-discharge synthesis of carbon nanomaterials from the carbon-containing gas in the form of a graph in which the technological operations of the subgroup responsible branches and stable states-vertices of the graph. Determine the coordinates of the state vector. This allows the process to present fragmentary, and using the decomposition method, the control problem broken down into multiple tasks of different levels, each of which relates to a specific fragment of the process is independent, has its own optimization criteria and algorithm implementation. Оperator control system provides a higher level of correlation between fragments model, setting conditional transitions from one fragment to another, imposing certain restrictions on incoming and outgoing coordinates. Provides conditions under which the subsystems are functioning in the specified mode according to the base algorithm and initial conditions.
Generalized model of control process of an electric-discharge synthesis of nanocarbon
Keywords: координати вектору стану; вершини графа; метод декомпозиції; ВНМ; coordinates of the state vector; decomposition method